Learning Entrepreneurship from Other Entrepreneurs? - Guiso, Luigi; Pistaferri, Luigi; Schivardi, Fabiano (Journal of Labor Economics, 2021)
We document that individuals who grow up in high firm density areas are more likely to become entrepreneurs, given firm density in their current location, and to run businesses in the sector with the highest density when young. Firm density at an entrepreneur’s young age drives current firm profitability and is more important than current density for business performance. Results hold in a sample of movers, which allows addressing endogeneity concerns. These results are consistent with entrepreneurial skills being partly learnable through social contacts. Accordingly, entrepreneurs who grow up in high firm density areas adopt better managerial practices.